Bilateral Recurrent Laryngeal Nerve Palsy following Total Thyroidectomy in Triple A Syndrome, an Unexpected but Critical Complication - Mathieu Chamberland; Marc-Antoine Poulin; Danielle Beaudoin (Case Reports in Otolaryngology)
Introduction. Triple “A” syndrome (TAS) is a rare autosomal recessive disorder that presents in childhood with achalasia cardia, alacrima, ACTH-resistant adrenal insufficiency, with sensorimotor and autonomic polyneuropathy developing later in the course of the disease. Case Presentation. An adult white male affected by this syndrome underwent an uneventful total thyroidectomy for malignancy and suffered delayed bilateral recurrent laryngeal nerve palsy in the early postoperative hours. The palsy spontaneously resolved after a five-week course. Conclusion. Given the rarity of this severe condition and the absence of surgical or medical causes identifiable, there is possibility that it is the neurological involvement caused by TAS that predisposed the patient to this adverse outcome, precipitated by standard manipulations during surgery.